Capital allocation, credit access, and firm growth in Viet Nam - Christina Kinghan; Carol Newman; Conor O'Toole (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In this paper, we explore the relationship between firm growth, access to finance, and the efficiency of capital allocation in Viet Nam over the period 2005-2015. Using data from the UNU-WIDER Viet Nam SME survey, we test whether firms with higher marginal returns to capital are more or less likely to get access to financing. This is a key test of how efficiently the financial system is functioning. We also test whether credit supply constraints are hindering capital allocation by limiting the investment and employment activities of firms with the highest marginal return on capital. A number of findings emerge. We find that high return investors, with the greatest marginal return on capital, have a lower likelihood of having formal finance (loans outstanding with formal credit institutions). We find evidence that rejected credit applications are limiting investment activity but not employment, particularly for firms with higher investment efficiency. This suggests a link between firm growth and a suboptimal allocation of credit.
Keywords: O12; O16; O17; 330; access to finance; SME; Viet Nam